Public perceptions towards oil palm cultivation in Tabasco, Mexico. (May 2018) - Pischke, Erin C.; Rouleau, Mark D.; Halvorsen, Kathleen E.
Abstract: National policies and international market demand have spurred a rapid increase in oil palm cultivation for biodiesel feedstock production, which then causes important social impacts. However, little work has investigated local perceptions of oil palm expansion, particularly in areas expected to become key supply regions, like Latin America. This limits our understanding of the social dimension of oil palm-based biodiesel sustainability. To address this oversight, we present findings from a survey of Tabasco, Mexico, that focuses on community perceptions of local oil palm plantations, their impacts, and expansion potential in a major oil palm cultivation region. We found that oil palm expansion-related perceptions were associated with attitudes toward existing oil palm plantations, whether the palm oil was being cultivated for biodiesel export, and oil palm's ecosystem service provision. Our findings highlight the need for policy makers to consider social acceptability when crafting strategies to expand sustainable bioenergy feedstock production. Highlights: Attitudes of palm oil biodiesel export linked to perceptions of oil palm expansion. Perceptions of oil palm expansion associated with attitudes of its ecosystem services. Social acceptance important when crafting strategies to grow oil palm sustainability.